PENGUATAN PERILAKU HIDUP SEHAT DAN BERSIH DI MASA PANDEMI COVID-19 - Agus Nugroho Setiawan (Universitas Muhammadiyah Tapanuli Selatan, 2021)
Pojok is one of village of Wonokerto, Turi, Sleman, DIY which is growing. The Pojok people realize that a good lifestyle will improve their health and a longer life expectancy, so they will continue to try to improve their knowledge and insight about health. Some of the problems faced are the insight and knowledge of the Pojok community about clean and healthy living behavior (PHBS) is still limited and has not been implemented as a whole, and family welfare program (PKK) activities related to clean and healthy living behavior and the number and skills of Health Cadres are still limited. To realize PHBS in Pojok, Community Service activities was conducted in the form of KKN PPM, for 6 months starting from January to June 2020. To achieve the goal, community service was conducted with several stages, i.e. KKN student training, coordination and socialization to the community, implementation of the field consisted as extension, training, facilitation, and assistance. The results of community service show that the activity has been going well with several activities, i.e. coordination, socialization, counseling, training and facilitation of supporting equipment, assistance, and monitoring and evaluation. The community of Pojok, Wonokerto, Turi gave a good response by participating in activities and implementing PHBS in their daily lives well. The community feels they have gained insight, experience and skills in the application of PHBS. The community service program of KKN PPM has provided more benefits, when the Covid-19 pandemic occurred, the community was ready to do a clean and healthy lifestyle